Corporate Social Responsibility of Russian TNCs as a Factor of Sustainable Development of Global Society - M. A. Izmailova (Модернизация, инновация, развитие, 2019)
Purpose: the main purpose of the study is to analyze the impact of corporate social responsibility of transnational corporations on the sustainable development of the territories of its presence and on its basis to develop recommendations for the integration of domestic business in the implementation of social projects abroad. In this regard, it is necessary to summarize the real experience and identify the best practices of Russian TNCs, positioning themselves as socially responsible companies.Methods: this article is based on the modern concept of corporate social responsibility – its understanding from the standpoint of the market approach to socially responsible behavior, state regulation of socially responsible practices, corporate conscience as a criterion of moral responsibility of the agent of economic relations, the theory of stakeholders, considering the Corporation as part of the social structure of society and responsible to a wide range of stakeholders. The study was conducted using the methods of comparative analysis, inductive-deductive and General logical methods.Results: the analysis of the impact of corporate social responsibility of transnational corporations on the sustainable development of the territories of its presence. The importance of the return of moral criteria in the economic sphere, which form the basis for assessing the level of socially responsible business behavior, is revealed. The article substantiates the increasing role of TNCs in the sustainable development of the global economy against the backdrop of a shortage of foreign direct investment needed to achieve sustainable development goals. The necessity of dialogue between TNCs and the national governments of the territory of their presence on a wide range of issues of support for the national economy, social investment in local communities and solving environmental problems is shown. The best practices of Russian TNCs in the field of corporate social responsibility are reviewed. The recommendations on the integration of domestic business in the implementation of social projects abroad.Conclusions and Relevance: one of the trends of sustainable development of the global economy is the recognition by economic agents of the importance and prospects of cooperation with ethically-oriented business, the imperative of which is corporate social responsibility. Investment by foreign affiliates of TNCs in the basic infrastructure, production capacity, social and environmental sphere of the territory of their presence should be considered from the perspective of corporate social responsibility. The content and volume of financing of corporate social responsibility programs by foreign affiliates of TNCs is largely determined by the specifics of the business. The implementation of corporate social responsibility, which has become part of the systematic approach of Russian business and is implemented within the framework of a common business strategy in foreign countries, is becoming an undeniable competitive advantage of Russian TNCs over foreign partners.